Disentangling Drought and Grazing Effects on Soil Carbon Stocks and CO2 Fluxes in a Semi-Arid African Savanna - Munjonji, Lawrence; Ayisi, Kingsley Kwabena; Mudongo, Edwin I.; Mafeo, Tieho Paulus; Behn, Kai; Mokoka, Malesela Vincent; Linstädter, Anja (Frontiers in Environmental Science, 2020)
Grasslands cover ca. 30% of the global land surface and provide critical ecosystem services. Among them, carbon storage is one of the most important. However, grasslands are increasingly threatened by drought and overgrazing which might negatively affect soil carbon stocks. Despite this threat, there is a dearth of information on how drought and grazing jointly impact soil carbon stocks and CO2 fluxes in dryland grasslands. With the aid of a large field experiment, we studied the combined effects of a five-year extreme drought and moderate grazing on soil carbon stocks, CO2 fluxes and soil chemical properties. Extreme drought was induced by reducing ambient rainfall by 66% using large rainout shelters. We found CO2 fluxes to strongly respond to the five-year experimental drought. Extreme drought reduced CO2 emission rates by 32% compared to ambient conditions. CO2 fluxes averaged 5.7 mg m-2min-1 under drought compared to 8.3 mg m-2 min-1 under ambient conditions. CO2 fluxes were however not influenced by grazing. At the end of the growth period, grazed plots under ambient rainfall had released 16.3 tons of CO2 ha-1 which was 58% higher than observed on grazed plots subjected to severe drought. Soil carbon stocks were higher under drought conditions due to slower decomposition rates. Drought resulted in increased concentrations of primary macronutrients (N, P, and K), micronutrients (Zn and Mn) and pH in the top 30 cm of the soil relative to ambient conditions. The results also showed that grazing reduced the concentration of N and P in the topsoil compared to the ungrazed plots. This study provided insights on the soil carbon storage, CO2 emission rates and nutrient dynamics in a semi-arid dryland grassland as influenced by both drought and grazing. Our study also revealed that long-term extreme drought may be favourable in terms of preserving the existing soil carbon stocks through reduced CO2 release. This finding is critical for understanding future soil carbon dynamics in dryland grasslands in the face of climate change.